Pengalaman Belanja Online Melalui Live Streaming Pada Media Sosial Tiktok Oleh Mahasiswa Ilmu Komunikasi Universitas Singaperbangsa Karawang - Adila, Muhammad Faza; Tayo, Yanti; Utamidewi, Wahyu (Jurnal Ilmiah Wahana Pendidikan, 2023)
Online shopping refers to the act of purchasing goods or services over the internet. It offers many benefits, including convenience, comfort, speed, and a wide variety of products to choose from. Online shopping can also save time and transportation costs. This study aims to investigate the motives, meanings, and experiences of individuals, specifically students of the Communication Studies Program at Singaperbangsa Karawang University, who engage in online shopping through live streaming on Tiktok social media. The study seeks to understand the reasons and motivations behind this behavior, as well as the experiences and perceptions of those who participate in it. This study uses a constructivism paradigm with a qualitative method. With Alfred Schutz’s phenomenological approach, it can be concluded that the motives for the informants to shop online through live streaming on Tiktok social media are due to the discounts offered and curiosity. The informants also have their own experiences, both positive and negative, that form meanings for the informants such as financial saviors, primary shopping places, and enjoyable shopping activities.